MACE-HEADS AND SIMILAR OBJECTS IN THE ANCIENT NEAR EAST ACCORDING TO WRITTEN SOURCES - Popko, Maciej (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2002)
Fluted maces (Kannelierte Streitkolben) have not been an object of a monographic study so far. The reasons for this deficiency was the paucity of assemblage finds (mainly grave ones) and the fact that they occurred in the borderland between the East and West of Europe. Both reasons made it difficult to identify them chronologically and keep a full record of finds. The present monograph sums up almost 25 years of studies that at the outset were limited to Poland and only gradually were expanded to include the whole continent. This was made possible owing to the goodwill of many people and institutions from the Danube area, the Balkans and the Russian Plain. The present volume of Baltic-Pontic Studies consists of two parts devoted, respectively, to the current state of knowledge on the position of the mace in the Near East and North Pontic civilizations, and the forms, chronology, origins, functions and socio-organizational significance of one of its types, namely the fluted mace. As in previous volumes in this series, our intention is to inspire team, interdisciplinary studies involving scholars from different centres and countries. Only such a wide-range co-operation will bring about new developments in the areas discussed in this volume.